The status quo in discrete choice experiments: is it relevant? - W Mohamad, Wan Norhidayah; Willis, Ken; Powe, Neil A. (World Scientific Publishing, 2019)
An issue in environmental economics is how respondents make choices in discrete choice experiments (DCEs), and whether different strategies impact on the reliability of willingness-to-pay (WTP) results. Do individuals make choices with reference to their status quo (SQ) position, or can they make simulated market choices amongst only hypothetical scenarios? This study uses a split sample to test whether the inclusion or exclusion of the SQ on a choice card in DCEs affects the WTP estimates, based on visitors’ preferences for tourist facilities at Kenyir Lake, Malaysia. The results indicated little difference between both the samples in terms of goodness-of-fit, size and significance of the attribute coefficients, and WTP estimates for the Conditional Logit (CL) and Mixed Logit (MXL) models.